Loss Modification Incentives for Insurers under Expected Utility and Loss Aversion - Adriaan R. Soetevent; Liting Zhou (Tinbergen Institute, 2014)
Given the possibility to modify the probability of a loss, will a profit-maximizing insurer engage in loss prevention or is it in his interest to increase the loss probability? This paper investigates this question. First, we calculate the expected profit maximizing loss probability within an expected utility framework. We then use Köszegi and Rabin's (2006, 2007) loss aversion model to answer the same question for the case where consumers have reference-dependent preferences. Largely independent of the adopted framework, we find that the optimal loss probability is sizable and for many commonly used parameterizations much closer to 1/2 than to 0. Previous studies have argued that granting insurers market power may incentivize them to engage in loss prevention activities, this to the benefit of consumers. Our results show that one should be cautious in doing so because there are conceivable instances where the insurer's interests in modifying the loss probability to against those of consumers.
Keywords: D11; D42; D81; L12; 330; loss modification; expected utility; reference-dependent preferences; insurance